Selective hydrogenation of chloronitrobenzenes with an MCM-41 supported platinum allyl complex derived catalyst - Indra, Arindam; Rajamohanan, Pattuparambil R.; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Applied Catalysis A-General, 2011)
A platinuin precatalyst (1) has been prepared by reacting [(eta(3)-C3H5)(4)Pt4Cl4] with surface functionalized MCM-41 with pendant -(CH2)(3)NH(CH2)(2)NH2 groups. For the hydrogenation of o-, m- and p-chloronitrobenzenes to the corresponding chloroanilines, 1 is found to be a highly active catalyst with good selectivities for them-and p-isomers. Its performance is superior to that of its palladium analogue and far superior to that of commercial (5%) Pt/C or (5%) Pt/Al2O3. Comparison of solid state and solution NMR data and other evidences indicate that on treatment with the functionalized MCM-41 support; [(eta(3)-C3H5)(4)Pt4Cl4] loses the ally! ligand. XPS data show that in the fresh catalyst Pt is present in the 2+ oxidation state. Based on these and analytical data, co-ordination by surface diamine and hydroxo groups to Pt2+ in 1 is suggested. In the used catalyst both Pt2+ and Pt are present but the amount of metallic platinum is similar to 16% of the total. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chloronitrobenzenes; Dehydrohalogenation; heterogeneous catalyst; MCM-41; Selective hydrogenation